The Students’ Perspective of Animated Learning Videos for Speaking Materials: English for Vocational Purposes - Astuti Pratiwi Rahmadhani; Fithratul Miladiyenti (International ABEC, 2022)
Powtoon online application. The analysis on the study is using qualitative methods with a case studyapproach This study reports an analysis of the participants’ perspective on the effectiveness of animated learning videoswhich was created by using. Respondents in this study involved participants from the English Department of StatePolytechnic of Padang. The result shows that the animation learning videos help the participants to understand thelearning material. The participants feel excited with the video and help them to learn the material by themselves orself-study. It indicates that animated learning videos assist students in comprehending the learning materials. The videogains the students' interest and encourages them to learn the material on their own or through self-study. Furthermore,it teaches students how to practice the expressions in a conversation for the purpose of improving their speaking skills.